Bridging the Knowledge–Practice Gap in Patient Education: Insights from Nurses in Eastern Saudi Arabia - Fouad, Rasha Ahmed; Almulhim, Aeshah Mohammed; Alrifai, Shahad Jomah; Aldarisi, Khadijah; Almarshud, Rawan; Albukhamsin, Sarah Adnan; Alyasin, Shahad; Alsalman, Mariam (Journal of Practical Nurse Education and Practice)

(untitled) (NorQuest College, 2026)
Patient education is vital for enhancing health outcomes and promoting patient autonomy. Despite nurses’ strong foundational knowledge and positive attitudes, a significant gap often exists between their understanding and practical clinical implementation. This study aimed to explore the knowledge, attitudes, and practices (KAP) of nurses concerning patient education within two National Guard hospitals in Eastern Saudi Arabia. A cross-sectional survey utilized a validated questionnaire with 275 nurses to assess their KAP. Data were analyzed using descriptive statistics, chi-square tests, and Pearson correlations. Nurses demonstrated high knowledge (90.5%) and positive attitudes (80%). However, only 57.1% reported satisfactory teaching practices, with younger and less experienced nurses facing particular challenges. A significant positive correlation (r = 0.200, p < 0.01) was found between knowledge and practice. To effectively bridge this knowledge–practice gap, targeted professional development programs, robust institutional support, and dedicated mentorship are crucial. Enhancing practical training and integrating patient education seamlessly into routine nursing workflows are key strategies for improving patient health outcomes.